1279 Improving adolescent wellbeing through reducing screen time usage. (17th August 2022) - Spence, James; Khan, Sadhia; Qiu, Connor; Watson, Mando
Abstract : Aims: The use of digital devices such as smartphone and tablets has increased substantially over the past few years (1). This has been well documented in the literature to have detrimental effects on all aspects of child and adolescent physical and mental health (2). Novel grassroots approaches to reduce screen time that are actionable in the local community with low-barriers to access can be effective, but requires significant further research (3). This study, inspired by design-thinking, uses qualitative and quantitative data, and coproduces new approaches to adolescent screen uses for clinical practice. Methods: Responding to an inner-city borough youth council's request for help to reduce screen time for Young Peoples (YP), data were collected through experience maps (n=4, aged: 11-14y) and an online focus group (n=18; aged: 12-21y). After further thematic analysis and discussion, suggested methods to reduce screen time were coproduced. This included pre and post questionnaires; smart aims; journaling and semi-structured discussions. Our proposed interventional framework incorporates the above to modify behaviour in this user group. Results: A majority of participants (89%) had insight into their screen time. Benefits noted included ease of communication, promoting independence, entertainment and learning. Negative effects included the addictive effect of devices, distraction and online bullying. Screen time use ranged between 1 – 9 hours; with 41% of participants spending 3 - 6 hours on their device. 53% of the total number of participants wished to cut down their use. Those using their screen for 1 - 3 hours (24%) felt that their use was acceptable. Iterative analysis and co-production continues. Conclusion: Approaching screen time in a novel and collaborative way encourages young people to modify their behaviour and device usage. The experience maps and focus groups identified the desire to reduce screen time and highlighted that young people feel ill-equipped to do so. Further work needs to be done in this space. This study identifies the need for a simple tool to address the impact of screen time on adolescent wellbeing and informs an interventional framework that can be effectively actioned in local child health hubs (4). The data gathered in this study will drive change in how clinicians engage with young people on this important and overlooked topic. References: Brodersen K, Hammami N, Katapally TR. Smartphone Use and Mental Health among Youth: It Is Time to Develop Smartphone-Specific Screen Time Guidelines. Youth. 2022;2(1):23-38. Twenge JM, Campbell WK. Associations between screen time and lower psychological well-being among children and adolescents: Evidence from a population-based study. Prev Med Rep. 2018;12:271-83. Farrell A, Tayler C, Tennent L. Building social capital in early childhood education and care: an Australian study. British educational research journal. 2004;30(5):623-32. Montgomery-Taylor S, Watson M, Klaber R. Child Health General Practice Hubs: a service evaluation. Archives of Disease in Childhood. 2016;101(4):333.